The Internet of Things security challenges - Đekić Milica D. (Tehnika, 2020)
The Internet of Things (IoT) is a quite recent paradigm going a decade back to the past. With the development and deployment of wireless technologies this new advancement has taken the part in the consumers' lives and businesses. In other words, the IoT is a pretty convenient way to correlated devices with each other and make them communicate in such a network. This is feasible using the internet connection and differently saying, all IoT devices forming the IoT asset got their IP addresses. From this perspective, it's quite clear that this technology got a lot of advantages and the users may feel so thankful for being the part of an IoT community. On the other hand, the consumers would spend less time thinking about the possible security concerns being linked to this new improvement. In this paper, we intend to discuss how secure our IoT infrastructure is, what its strategic implications are and why cyber industry should invest more time and effort in order to better research and develop this concept. In addition, we would try to deal a bit more with the IoT crawlers as the tools for investigating the IoT network and being so handy for both - researchers and hacker's groups.